Prevalence and correlates of anxiety and depression among chronically ill older adults in Zunyi, China: a cross-sectional study - Xiaoling Zhao; Xiaoling Zhao; Xiaoling Zhao; Xiaoli Yuan; Dan Meng; Heting Liang; Yan Xiong; Yan Xiong; Yunting Li; Yunting Li; Shuang Li; Mei He; et al. (Frontiers in Psychology)
BackgroundAgainst the background of an aging population, the prevalence of mental health problems among elderly people with chronic diseases is steadily increasing. The prevalence of mental health problems is higher in less economically developed regions, but there are still limited reports on the mental health data of elderly people with chronic diseases in less developed western regions.ObjectiveTo find out the prevalence of anxiety and depression among chronically ill elderly people in Zunyi, China, and to analyze the risk factors for the prevalence of anxiety and depression.MethodsA stratified randomized whole-cluster sampling method with face-to-face questionnaires was used to survey people aged 60 years and older with chronic diseases in Zunyi, China, from March 2022 to October 2023. Relevant demographic and clinical data were collected using structured questionnaire contents of sociodemographic characteristics, Self-Assessment Scale for Anxiety (SAS), Geriatric Depression Scale (GDS-15), Brief Miniature Nutritional Assessment Scale (MNA-SF), Pittsburgh Sleep Quality Index (PSQI), Barthel Index (BI), etc., and bivariate analyses were carried out to explore the anxiety according to the different characteristics of the subjects Bivariate analyses were conducted to explore the differences in anxiety and depression according to the different characteristics of the subjects, and multifactorial logistic regression analyses were conducted to test the factors affecting anxiety and depression.FindingsA total of 9,998 subjects were enrolled in this study, and 9,821 valid questionnaires were obtained. The prevalence of anxiety was 26.83% (95% CI: 26.00–27.70), the prevalence of depression was 10.33% (95% CI: 9.70–10.90), and the prevalence of anxiety combined with depression was 6.88% (95% CI: 6.40–7.40). The chronic diseases included in this study encompass cardiovascular diseases, endocrine system diseases, cerebrovascular diseases, degenerative diseases, respiratory system diseases, digestive system diseases, kidney diseases, and cancer. Compared to patients with other chronic diseases, those suffering from cardiovascular diseases exhibit a higher prevalence of anxiety, depression, and the co-occurrence of both anxiety and depression. The results of multifactorial logistic regression analysis showed that advanced age, high literacy, high average monthly household income, regular physical exercise, adequate material and emotional support, and mild dependence in daily life were protective factors for depression among chronically ill older adults (P < 0.05). Living in rural areas, moderate ability to perform activities of daily living, heavy dependence, poor self-assessed health, presence of malnutrition, presence of debilitation and in the pre-debilitating stage, and presence of sleep disorders were independent risk factors for depression in chronically ill older adults (P < 0.05). High literacy, high average monthly family income, regular physical exercise, regular social activities, sufficient material and emotional support, living in a nursing facility, and mild dependence in daily life were protective factors for anxiety in chronically ill older adults (P < 0.05). Advanced age, childlessness, moderate ability to perform activities of daily living, heavy dependence, poor self-assessed health, the presence of malnutrition, the presence of infirmity and pre-infirmity, and the presence of sleep disorders were independent risk factors for anxiety in chronically ill older adults (P < 0.05).InterpretationThe prevalence of anxiety among elderly individuals with chronic diseases in Zunyi City, China, is higher than the global average, whereas the prevalence of depression is lower than the global level. Patients with cardiovascular diseases exhibit a higher prevalence of anxiety, depression, and the co-occurrence of both anxiety and depression. Factors such as economic income, education level, lifestyle habits, and medical history influence the occurrence of anxiety and depression in elderly individuals with chronic diseases. This highlights the need to promote screening for anxiety and depression among the elderly with chronic conditions and to enhance community awareness of mental health issues in the elderly population.